Yolk sac tumor of the external auditory canal: a case report and literature review - Shi, Huijuan (Int J Clin Exp Pathol, 2015)
We report one case of yolk sac tumor of the ear and review the literature. The patient was a 9-month boy who scratched his right ear repeatedly one month ago. Computed tomography scan showed an irregular elongated mass image measuring 42×16 mm was found in the right external auditory canal. The tumor was located underneath of the epidermis with ulceration. Mild or moderate atypical round or oval tumor cells were arranged in nest and reticular pattern around vesicular or cystic spaces. Tumor cells had abundant eosinophilic or clear cytoplasm and marked nucleoli. Mitotic figures were about 7/10HPF. Poorly formed Schiller-Duvall body was occasionally present. The stroma was loose and rich in capillaries. Hyaline globules could be found in the stroma. Immunohistochemistry staining showed that tumor cells were positive for cytokeratin, SALL4, glypican-3, focal positive for EMA, vimentin, CD10, and CD34, but negative for a-fetoprotein, HCG, PLAP. The serum α-fetoprotein was 664.60 ng/mL (normal, ≤25 ng/mL). Yolk sac tumor of the ear is extremely rare, especially α-fetoprotein negative expression in our case. The differential diagnosis includes embryonal rhabdomyosarcoma, paraganglioma, myoepithelioma, carcinoma of skin appendages, and metastatic renal cell carcinoma.